Integrating patient- and caregiver-reported outcome measures into the daily care routines of specialised outpatient palliative care: a qualitative study (ELSAH) on feasibility, acceptability and appropriateness - Hannah Seipp; Jörg Haasenritter; Michaela Hach; Dorothée Becker; Dania Schütze; Jennifer Engler; Cornelia Ploeger; Stefan Bösner; Katrin Kuss (BMC Palliative Care, 2022)
Abstract Background The use of patient-reported outcome measures (PROM) and caregiver-reported outcome measures can raise the patient centeredness of treatment and improve the quality of palliative care. Nevertheless, the everyday implementation of self-report in patients and caregivers is complex, and should be adapted for use in specific settings. We aimed to implement a set of outcome measures that included patient and caregiver self- and proxy-reported outcome measures in specialised outpatient palliative care (SOPC). In this study, we explore how the Integrated Palliative Outcome Scale (IPOS), IPOS Views on Care (IPOS VoC) and the Short-form Zarit Caregiver Burden Interview (ZBI-7) can be feasibly, acceptably and appropriately implemented in the daily care routines of SOPC. Methods Five SOPC teams were trained, and used the outcome measures in daily practice. Team members were mainly nurses and physicians. To investigate their feedback, we used a multi-method qualitative design consisting of focus groups with SOPC-team members (n = 14), field notes of meetings and conversations with the SOPC teams. In an iterative process, we analysed the findings using qualitative content analysis and refined use of the outcome measures. Results We found that integrating patient and caregiver outcome measures into daily care routines in SOPC is feasible. To improve feasibility, acceptability and appropriateness, the resulting burden on patients and relatives should be kept to a minimum, the usefulness of the measures must be understood, they should be used considerately, and administration must be manageable. We removed ZBI-7 from the set of measures as a result of feedback on its content and wording. Conclusions SOPC-team members have reservations about the implementation of PROM in SOPC, but with appropriate adjustments, its application in daily care is feasible, accepted and perceived as appropriate. Previous to use, SOPC-team members should be trained in how to apply the measures, in the design of manageable processes that include integration into electronic documentation systems, and in ongoing evaluation and support. They should also be taught how useful the measures can be. Trial registration May 19th, 2017, German Clinical Trials Register DRKS-ID: DRKS00012421 .